1
$\begingroup$

Show $$\lim_{(x,y)\to (0,0)} xy \frac{(x+y)}{x^2-xy+y^2}=0$$

If I approach from $y=\pm x$, I get $0$. Is that sufficient?

$\endgroup$
1
2
$\begingroup$

From $\bigl(|x|-|y|\bigr)^2\geq0$ we get $2|xy|\leq x^2+y^2$ and then $$|x|+|y|\leq\sqrt{2(x^2+y^2)},\qquad x^2-xy+y^2\geq{1\over2}(x^2+y^2)\ .$$ This implies $$\bigl|f(x,y)\bigr|=\left|{xy(x+y)\over x^2-xy+y^2}\right|\leq{{1\over2}(x^2+y^2)\sqrt{2(x^2+y^2)}\over{1\over2}(x^2+y^2)}=\sqrt{2(x^2+y^2)}\ .$$ Therefore, given an $\epsilon>0$, we have $\bigl|f(x,y)\bigr|<\epsilon$ as soon as $\sqrt{x^2+y^2}<\delta:={\displaystyle{\epsilon\over\sqrt{2}}}$.

$\endgroup$
1
  • $\begingroup$ Aren't you kind of giving away the answer ? Why not suggest epsilon-delta and let OP work it out? Is that not how things are done on MSE? $\endgroup$
    – user198044
    Mar 23 '15 at 9:59
2
$\begingroup$

No, that is not sufficient. That can only show that if the limit exists, then it should equal $0$. But it doesn't show that the limit exists.

Change to polar coordinate system, so that

$$ \lim_{(x,y)\to (0,0)} \frac{xy(x+y)}{x^2-xy+y^2} = \lim_{r\to 0} \frac{ (r^2 \sin \theta \cos \theta) (r\sin \theta + r\cos \theta)}{r^2-r^2\sin \theta \cos \theta}= \lim_{r\to 0} \frac{r\sin \theta \cos \theta(\sin \theta + \cos \theta)}{1-\sin \theta \cos \theta} $$

(Check that two limits are equilvalent from the ($\varepsilon$-$\delta$) definition of the limits)

But notice that $|1-\sin \theta \cos \theta|=|1-\sin (2\theta) /2|\ge 1/2$.

Hence $\displaystyle \frac{\sin \theta \cos \theta(\sin \theta + \cos \theta)}{1-\sin \theta \cos \theta}$ is bounded for all $\theta\in \mathbb{R}$, and so

$$ \lim_{r\to 0} \frac{r\sin \theta \cos \theta(\sin \theta + \cos \theta)}{1-\sin \theta \cos \theta}=0 $$

$\endgroup$
1
  • $\begingroup$ Aren't you kind of giving away the answer ? Why not suggest polar coordinates and let OP work it out? Is that not how things are done on MSE? $\endgroup$
    – user198044
    Mar 23 '15 at 9:59
1
$\begingroup$

Let $t=\frac yx$. (Note the we can do this only for $x\ne0$. But $x=0$ should not be a problem, since the whole expression is zero in that case.)

Then we have $$\frac{xy(x+y)}{x^2-xy+y^2}=\frac{x^3}{x^2} \cdot \frac{t(1+t)}{1-t+t^2}$$ If we can show that the expression $$g(t)=\left|\frac{t(1+t)}{1-t+t^2}\right|$$ is bounded, then this is sufficient to show that the limit is zero.

For example:

  • Can you show that for $t\le\frac12$ you have $|t^2-t| \le t^2-t+1$, which means that in this case we have $g(t)<1$?
  • Can you show that for $t>\frac12$ the value $g(t)$ is positive and $t^2+t<3(t^2-t+1)$, which means that $g(t)<3$?

Or simply try some other way to show that this expression is bounded.

If will add plot form WA:

plot of the 3 functions

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.